A Criminological Review: Exploring Community Perception of Juvenile Delinquency in Panenjoan Village - Eki Furqon; Alycia Risaldy Halim; Fuad Sirojul Huda; Nisrina Agustini; Syifa Aulia Nur Fadlilah; Muhamad Farhan Al Amien; Ratri Yulianingsari Negoro; Santomi Santomi; Yunita Yunita; Aqila Zahra; Diska Eunike; Aisa Aulina (Probono and Community Service Journal, 2022)
Juvenile delinquency is becoming one of the urgencies that must be considered by us, especially in Panenjoan Village. With the development of the times, these teenagers will get convenience in any case. Including to do negative things. As is being hotly reported on television, there are a lot of juvenile delinquency acts that are troubling the surrounding residents. The purpose of this study is to find out what juvenile delinquency occurs in Panenjoan Village as well as to know the perception of the community regarding the occurrence of juvenile delinquency which is quite large in percentage. This study uses the Community Education method by conducting socialization related to juvenile delinquency with the theme "Young Generations of Moral and Quality" where this socialization is a form of providing more knowledge to the harvested village youth and data collection and analysis techniques with qualitative data, namely direct interviews as well as surveys. The results of the activities carried out are the socialization of juvenile delinquency. One of them is promiscuity which produces the highest percentage of juvenile delinquency that occurs in Panenjoan Village. This makes many teenagers, especially women who get pregnant out of wedlock due to promiscuity. Based on the results of this data, we students get the factors that cause juvenile delinquency, one of which is family and environmental factors. Community perceptions based on the results of surveys and community interviews are also about juvenile delinquency that occurs, namely the community is very unfortunate with juvenile delinquency that occurs due to family and environmental factors, according to the community many children also drop out of school due to juvenile delinquency that occurs. The community looks sad and asks for help related to preventing juvenile delinquency. To prevent delinquency, more knowledge is needed regarding the good and bad in society, especially for teenagers, knowing in morals to become quality teenagers without juvenile delinquency